Impact of Obstetric Cholestasis on Fetomaternal Outcome - Anwar, Rabiah; Razzaq, Kashif; Noor, Nusrat; Ansari, Asma; Imran, Ayesha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the impact of obstetric cholestasis on maternal and fetal outcomes.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Gynaecology and Obstetrics, Pakistan Naval Ship Shifa Hospital Karachi Pakistan, from Jan to Dec 2019.Methodology: All pregnant women with no comorbid and ladies with symptoms and signs of obstetric cholestasis were included during the study period. Antenatal complications and perinatal outcomes of women having obstetric cholestasis were compared with those of pregnant ladies having no comorbid.Results: Out of 6932 obstetric patients, 90 (1.29%) had obstetric cholestasis. The cholestatic group had significantly high levels of aminotransferases and alkaline phosphatase. There was higher occurrence of preterm prelabour rupture of membrane (11.11% vs 3.33%, p=0.044), preterm delivery (26.66% vs 4.44%, p